Evaluation of the anaerobic digestion of kitchen waste by thermal pretreatment in a batch leach bed reactor with down flow and the kinetics of methane yields. Issue 3 (4th May 2018) - Alizadeh, Hossein H. A.; Seifi, Rahman; Radmard, Seyed Abbas
ABSTRACT: The aim of this study was to evaluate the effects of autoclave and microwave irradiation (MW) pretreatments on the solubilization, biogas and methane yields of kitchen waste (KW). Autoclave (for 30 min @ 120, 1 bar) and MW (for 400 s @ 80, 700 W) pretreatments were used to enhance anaerobic digestion of KW. The anaerobic digestion of KW in autoclave and MW pretreatments were compared with a control in a batch leach bed reactor with down flow (LBR DF). During autoclave and MW pretreatments, the biogas yields were respectively 25.41 and 41.43% higher than the control test and for methane were respectively 22.73 and 38.91% higher than the control test. The highest solubilization efficiency was obtained after MW pretreatment (89.21%), followed by after autoclave pretreatment (85.73%), and the lowest value was obtained with control (61.37%). Mathematical models fitted experimental data with R 2 >0.9798. The present study shows that autoclave and MW pretreatments can be used to improve biogas and methane yields and solubilization efficiency. Schnute and modified Gompertz models gave a good fit of the first stage of fermentation as well as the asymptotic phase.